1996
DOI: 10.1021/ma951394v
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Optically Active Polyamides Derived from Di-O-methyl-l-tartaric Acid and 1,n-Alkanediamines:  A Study Combining Energy Calculations, Diffraction Analysis, and Modeling Simulations

Abstract: The crystal structures of a series of optically active polyamides derived from l-tartaric acid and 1,n-alkanediamines (n = 2, 4, 6, and 8) have been investigated. Experimental data provided by X-ray diffraction of powders and fibers as well as by electron diffraction of single crystals were used to determine the lattice parameters for each polymer. A triclinic unit cell with space group P1 was found to be shared by the whole series. Semiempirical quantum mechanical calculations revealed that the preferred conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 32 publications
4
40
1
Order By: Relevance
“…This is a remarkable feature displayed by tartaric acid based polyamides that has previously been noticed in similar studies carried out on related systems. [19] The carbon spectrum contains all the peaks arising for every magnetically different carbon present in the repeating unit. A reliable complete assignment of peaks could be done with the help of two-dimensional techniques which revealed that, contrary to expectations, the resonance due to the amide carbons are those appearing downfield to ester carbons.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…This is a remarkable feature displayed by tartaric acid based polyamides that has previously been noticed in similar studies carried out on related systems. [19] The carbon spectrum contains all the peaks arising for every magnetically different carbon present in the repeating unit. A reliable complete assignment of peaks could be done with the help of two-dimensional techniques which revealed that, contrary to expectations, the resonance due to the amide carbons are those appearing downfield to ester carbons.…”
Section: Synthesismentioning
confidence: 99%
“…Although no detailed structural analysis has been carried out on any poly(ester amide)s containing tartaric acid, diffraction data recorded from random poly(tartarester amide)s of 1,6-hexanediol and 1,6-hexanediamine containing up to 20% of succinic acid [15] have proved that they adopt a crystal structure close to the triclinic structure described for the homopolyamide poly(hexamethylene di-O-methyl-L-tartaramide). [19] In such a structure the polyamide chains are somewhat contracted due to the gauche conformation adopted by the tartaric moiety and hydrogen bonds are aligned along one unique direction.…”
Section: Polymermentioning
confidence: 99%
“…A common type of crystal structure seems to be adopted by all a-PEAT6(a : b) poly(tartarester amide)s, regardless of the chemical composition and regicity, and this structure is very close to that adopted by the polyamide P6DMLT. 4 The crystal structure of this polyamide was investigated in detail by us a few years ago and was determined to be a structure made of hydrogenbonded sheets with chains in a slightly contracted conformation. The structure is similar to that described for the well-known ␣ form of nylon-6,6.…”
Section: Crystalline Structurementioning
confidence: 99%
“…3 Among them, poly(hexamethylene-di-O-methyl-L-tartaramide) (P6DMLT), which is made from 1,6-hexanediamine and L-tartaric acid, is particularly interesting. 3,4 This poly(tartaramide) is highly crystalline, melts at 230°C, and may absorb up to 10% water when exposed to a humid atmosphere. However, it degrades very slowly in neutral water, losing less than 10% of its initial weight after 1 year of incubation.…”
Section: Introductionmentioning
confidence: 99%
“…Progress in polymer chemistry has allowed the synthesis of entirely different condensation polymers which one of them is optically active polyamides (PA)s [47]. Many studies concerned with the synthesis and characterization of optically active PAs have been undertaken [48][49][50][51][52][53][54][55], mainly polypeptides and proteins which have been extensively investigated. Synthesis and optical properties of asymmetric PAs derived from composed of optically active cyclic dicarboxylic acids, (+)-(S)-and (-)-(R)-trans-1,2-cyclopropanedicarboxylic acids, (-)-(R)-trans-1,2-cyclobutanedicarboxylic acids, (+)-and (-)-trans-1,3-cyclopentanedicarboxylic acids and secondary diamines such as trans-2,5-piperazine, piperazine or N,N!-dimethylethylenediamine was reported by Overberger and Shimokawa [56].…”
Section: Synthetic Optically Active Condensation Polymers 21 Polyammentioning
confidence: 99%